SAT0127 Patients with Rheumatoid Arthritis Show Significantly Worse Subclinical Vascular Damage than Healthy and Hypertensive People. (9th June 2015) - Robustillo Villarino, M.; Rodilla Sala, E.; Gil Latorre, F.; Ybañez Garcia, M.D.; Martínez Ferrer, M.A.; Valls Pascual, È.; Vicens Bernabeu, E.; Vergara Dangond, C.; Alber Espí, G.; Alegre Sancho, J.J.
Abstract : Background: Rheumatoid arthritis (RA) is associated with a significantly enhanced risk of atherosclerotic cardiovascular (CV) disease that contributes to morbidity and mortality. Pulse wave velocity (PWV), common carotid intima-media thickness (cIMT), and the detection of atherosclerotic plaques by carotid ultrasound are tools to determine vascular damage in preclinical stages of atherosclerotic disease. Vascular damage is increased in patients with RA and other illnesses with elevated CV risk, like hypertension. Objectives: To assess the presence of vascular damage alterations in carotid ultrasound and determination of PWV in patients with RA as compared with healthy and hypertensive (HT) controls group. Methods: We evaluated 181 consecutive patients with RA without clinical artery disease (cardiovascular events: ischemic heart disease or stroke), diabetes mellitus (DM), or severe chronic renal disease (defined by a glomerular filtration rate <60), who were controlled in a tertiary outpatient hospital. Healthy control group and HT patients were evaluated in an internal medicine department, both groups belonging to a population from a region from the east of Spain. Statistical analysis was adjusted for demographic variables (age, gender, BMI), smoking history, cholesterol fractions, clinical variables (central and peripheral systolic blood pressure (SBP)). The ultrasound study was performed with an Esaote MyLab xv70 ultrasound equipped with a 7-12 mHz linear transducer. An automated program assessed the IMT through radiofrequency (Quality intima media thickness in real time [QIMT]). Measurements were done at the bilateral common carotid artery, and presence of atheroma plaque in the extra cranial carotid artery was registered following the Manheim consensus. PWV measurements were performed, three per patient while seated, of which the last two were used. PWV was determined by a validated MobilOGraph® device. Patients were classified as having high CV risk if PWV≥10m/s. Statistical analysis was performed using the SPSS 17.0 program. Results: Analysis of clinical and vascular variables are listed below: Statistically significant differences were found between groups of healthy patients and those with HT and RA in relation to demographic variables and vascular damage (cIMT, presence of plaques, PWV). Given the age difference between the groups, a statistical analysis was performed to adjust for differences in age, yet they still maintained the differences. Conclusions: Patients with RA have higher cIMT than healthy population and hypertensive patients. Both genetic polymorphisms and chronic inflammation may explain these differences. Further studies are required to evaluate the differences between variables of vascular damage like PWV and the presence of plaques. Disclosure of Interest: None declared